PENGARUH GAYA KEPEMIMPINAN, PENGETAHUAN PRINSIP DASAR PLS, DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI PENGELOLA PUSAT KEGIATAN BELAJAR MASYARAKAT - Fakhruddin Fakhruddin (Jurnal Ilmiah Visi, 2010)
The objective of this research is to find out the effect of leadership style, knowledge of the basic principles of non-formal education, and work motivation on organizational commitment of Community Learning Centre (CLC) Managers in Jakarta. This research was conducted in DKI Jakarta, on March to August 2009. The data was collected from 85 managers as sample and selected by simple random sampling . The result of this research are as follows: (1). The leadership style of CLC managers has direct effect on work motivation; (2). knowledge about of basic principles of non-formal education has direct effect on work motivation; (3). Work motivation has direct on organizational commitment of CLC managers; (4). The leadership style has direct effect on organizational commitment of CLC managers; (5). Knowledge about of basic principles of non-formal education has direct effect on organizational commitment of CLC managers; (6). The leadership style of CLC managers has indirect effect on organizational commitment of CLC managers, Through work motivation and (7) Knowledge about of the basic principles of non- forma/ education has indirect effect on organizational commitment of CLC managers through work motivation. Therefore, it could be concluded that the increasing of or decreasing of organizational commitment effected directly or indirectly by leadership style, knowledge about the basic principle of Non Formal Education and work motivation. This conclusion implies that when we want to improve the organizational commitment, we have to take into consideration those three variables, leadership style, knowledge about the basic principle of non formal education and work motivation as well.